"The thing I'm missing the most is just being around other queer people": critical analysis of the impacts of the COVID-19 pandemic on mental health of two-spirit, gay, bisexual, and queer men's communities in Manitoba, Canada - Rusty Souleymanov; Samantha Moore; Jared Star (BMC, 2023)
Abstract Background The purpose of this community-based study was to create and advance knowledge on the social impacts of COVID-19 on mental health of Two-Spirit, gay, bisexual, and queer (2SGBQ+) cisgender and transgender men in Manitoba, Canada. Methods Participants (n = 20) from 2SGBQ + men's communities were recruited across Manitoba using printed flyers and social media. Individual interviews explored questions relating to the impacts of the COVID-19 pandemic on mental health, social isolation, and service access. Data were critically examined using thematic analysis and the social theory of biopolitics. Results Key themes focused on COVID-19 pandemic's negative impacts on 2SGBQ + men's mental health, loss of safe queer public spaces, and exacerbated inequities. During the COVID-19 pandemic in Manitoba, 2SGBQ + men experienced a profound loss of social connections, community spaces, and social networks which are specific to their socio-sexual identities, thereby intensifying pre-existing mental health disparities. These findings show how COVID-19 restrictions have come to reinforce the value of close personal communities, families of choice, and social networks among 2SGBQ + men in Manitoba, Canada. Conclusions This study supports the line of research on minority stress, biosociality, and place by highlighting some potential links between 2SGBQ + men's mental health and their social and physical environments. This research points to important role of safe community spaces, events, and community organizations that support 2SGBQ + men's mental health.